Release: Major Aboriginal Sculpture Unveiled - External Relations, University of Regina (External Relations, University of Regina, 2005)
A major aboriginal sculpture has been unveiled on the grounds of the University of Regina. The "Four Directions" sculpture is one of the largest publicly commissioned pieces of art work awarded to a First Nations artist in Saskatchewan. Staff no